2020
DOI: 10.3345/kjp.2019.00024
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of interhospital transport care for pediatric patients

Abstract: Background: Many critically ill patients require transfer to a higher-level hospital for complex medical care. Despite the publication of the American Academy of Pediatrics guidelines for pediatric interhospital transportation services and the establishment of many pediatric transport programs, adverse events during pediatric transport still occur.Purpose: To determine the incidence of adverse events occurring during pediatric transport and explore their complications and risk factors.Methods: This prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…The results of this study indicated that device preparation was the dominant factor for AEs during the transfer of critically ill patients from the emergency room to the intensive care unit. These results are in line with other studies, which state that adverse events that occur during intrahospital transportation are caused by the unavailability of equipment (Chaichotjinda et al, 2020). Adequate equipment preparation increases patient safety and security during intra-hospital transfers (Swickard et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…The results of this study indicated that device preparation was the dominant factor for AEs during the transfer of critically ill patients from the emergency room to the intensive care unit. These results are in line with other studies, which state that adverse events that occur during intrahospital transportation are caused by the unavailability of equipment (Chaichotjinda et al, 2020). Adequate equipment preparation increases patient safety and security during intra-hospital transfers (Swickard et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…In a study done in Thailand, the main diagnostic categories that required transport to a higher level of care were neurological conditions, respiratory, hematooncologic, and cardiac illness. 22 In countries like the United States, 1 study reported that asthma, epilepsy, and diabetes mellitus were the most common pediatric interfacility transport diagnosis, and children aged 0 to 4 years were the ones that were more commonly transferred to another facility than patients from another age group. In this study, they applied an interfacility transport rate, and the 3 categories with the highest rate were diabetes mellitus, appendicitis, and internal obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…While necessary in some cases for optimal patient health, the transfer process may put the patient at risk for adverse events. Patients often undergo repeated, unnecessary laboratory and radiologic tests at the destination hospital, 6–9 which sometimes place significant emotional and financial burdens on the patient's family. These considerations are particularly relevant for rural families given the additional travel and lodging needs 4 …”
mentioning
confidence: 99%
“…Several professional organizations recognized the pediatric‐specific challenges of emergency care and formed the National Pediatric Readiness Project (NPRP), a multiphase quality improvement collaborative aimed at improving pediatric emergency care. The NPRP established a survey‐based quantitative measure of pediatric readiness that evaluates ED compliance with the 2009 “Guidelines of Care of Children in the Emergency Department.” 10 Recent studies have found that EDs with increased pediatric readiness were associated with decreased hospital length of stay and decreased mortality 7,11 …”
mentioning
confidence: 99%